Evaluation of Surface Doses and Effect of Air Gaps Under Bolus during External Photon Beam Radiotherapy - Odartey, L.P.N. (University of Ghana, 2018)
This study was performed to evaluate surface doses and the effect of air gaps under bolus on surface dose during external beam radiotherapy for photon beam energies of 6 MV and 15 MV. Surface doses were measured by using calibrated GafChromic EBT3 films and the Roos chamber for various bolus-to-surface distances (including no bolus and bolus placed directly on the RW3 phantom surface) and various field sizes. Dose verification was also done for beam energies of 6 MV and 15 MV on the RANDO phantom by measuring doses at dmax using a diode. The introduction of the bolus increased the surface dose for all field sizes and beam energies. For 5×5 cm2 the surface dose increased by 61% and 72% with the introduction of the bolus for 6 MV and 15 MV respectively using the Roos chamber. For both 6 MV and 15 MV, surface doses increased significantly with the introduction of the bolus. Also, due to more skin sparing in 15 MV than 6 MV, surface doses recorded for the 6 MV photons were generally of higher value than those for the 15 MV photons especially for field sizes that were smaller. As the bolus-to-surface distance increased, the doses recorded at the surface decreased. This decrease however was seen for the small field sizes (5×5 cm2 and 10×10 cm2). For field sizes that were larger (15×15 cm2 and 20×20 cm2) the change in dose to the surface as a result of change in air gap was negligible. For 5×5 cm2, dose to the surface decreased by 21% and 33% with a 5 cm air gap for 6 MV and 15 MV respectively compared to 20×20 cm2 field, where the change was negligible with only a 2% and 1% increase in surface dose recorded for both 6 MV and 15 MV respectively when the ion chamber was used. The field size of 5×5 cm2 showed the most variation of surface dose with changing air gaps showing that change in skin dose as a result of air gaps is only significant for small field sizes.
Thesis (MPhil)
Keywords: Air Gaps; Radiotherapy; Photon Beam; Bolus during External; Evaluation